2015
DOI: 10.1017/ice.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Epidemiology of Carbapenem-ResistantEnterobacterInfections: A Multicenter Descriptive Analysis

Abstract: In this study conducted at 2 distinct CRE endemic regions, there were unique epidemiologic features to CREn: (i) polyclonality, (ii) neonates accounting for more than 7% of cohort, and (iii) high rate of colonization (almost one-half of all cases represented colonization). Since false-positive Modified Hodge Tests in Enterobacter spp. are common, close monitoring of carbapenem resistance mechanisms (particularly carbapenemase production) among Enterobacter spp. is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Patient-to-patient transmission is an important mode for acquisition of carbapenemresistant E. cloacae (23,25), but transmission from the hospital environment may occur since room surfaces in surroundings of CRE carriers have been frequently identified as contaminated (26). On the other hand, our previous study showed that CRE (Enterobacter and Klebsiella species) survived poorly in a hospital environment for 24 h and was infrequently isolated from environmental surfaces in rooms housing CRE-colonized/ infected patients (27); thus, the role of hospital environmental surfaces for CRE transmission is yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-to-patient transmission is an important mode for acquisition of carbapenemresistant E. cloacae (23,25), but transmission from the hospital environment may occur since room surfaces in surroundings of CRE carriers have been frequently identified as contaminated (26). On the other hand, our previous study showed that CRE (Enterobacter and Klebsiella species) survived poorly in a hospital environment for 24 h and was infrequently isolated from environmental surfaces in rooms housing CRE-colonized/ infected patients (27); thus, the role of hospital environmental surfaces for CRE transmission is yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, Enterobacter spp. are the sixth leading cause of health care-associated infections globally (8). …”
Section: Introductionmentioning
confidence: 99%
“…Recent surveillance studies have shown that Enterobacter spp. are often the second or third most common Enterobacteriaceae species associated with carbapenemases ( 3 , 4 ). Typically, KPCs are common among Enterobacter spp.…”
mentioning
confidence: 99%